2013
DOI: 10.1007/s10661-013-3537-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of chlorantraniliprole granule formulation in sugarcane field soil

Abstract: Chlorantraniliprole, an anthranilic diamide insecticide with novel mode of action, is found effective against several lepidopteran as well as coleopteran, dipteran, and hemipteran pests. The present studies were carried out to study the persistence pattern of chlorantraniliprole on sugarcane field soil following application of granule formulation. The residues of chlorantraniliprole were estimated using high performance liquid chromatograph (HPLC) and confirmed by liquid chromatograph-mass spectrometry (LC-MS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Zhang and others studied the recovery of CAP in rice field ecosystem and they reported that the recovery was ranged from 76.90 to 103.10% at 0.0001 to 0.1 mg/kg (Zhang et al 2012). Sharma and co-authors studied the recovery of CAP in sugarcane field soil and they found that the recovery was ranged from 87.29 to 95.80% at 0.01 to 1.00 mg/kg (Sharma et al 2014b). Wang and Zhang studied determination of the dissipation dynamics and residue behaviors of CAP in soil by LC-MS/MS they found that the recovery was ranged from 81.90 to 97.7% at 0.010 to 4.00 mg/kg (Wang and Zhang 2017).…”
Section: Hplc Methods Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang and others studied the recovery of CAP in rice field ecosystem and they reported that the recovery was ranged from 76.90 to 103.10% at 0.0001 to 0.1 mg/kg (Zhang et al 2012). Sharma and co-authors studied the recovery of CAP in sugarcane field soil and they found that the recovery was ranged from 87.29 to 95.80% at 0.01 to 1.00 mg/kg (Sharma et al 2014b). Wang and Zhang studied determination of the dissipation dynamics and residue behaviors of CAP in soil by LC-MS/MS they found that the recovery was ranged from 81.90 to 97.7% at 0.010 to 4.00 mg/kg (Wang and Zhang 2017).…”
Section: Hplc Methods Validationmentioning
confidence: 99%
“…Zhang and other calculated the half-life of CAP in soil of rice field ecosystem to be 16.0 days (Zhang et al 2012). Malhat et al studied the results showed half-life value of 3.30 and 3.66 days for CAP in tomato fruit and soil ) and the dissipated in tomato fruit and soil followed the first order kinetics Sharma et al 2014b). Vijayasree et al and Ramasubramanian et al reported that CAP dissipated rapidly in cowpea fruits, with a half-life of 1.31 day and persisted in soils of sugarcane with longer half-life of 6.5-6.8 days (Ramasubramanian et al 2012;Vijayasree et al 2013).…”
Section: Figure 3 Dissipation Curves Of Cap In Soil a And B With Or mentioning
confidence: 99%
See 1 more Smart Citation
“…However, no ecotoxicity data are available for other soil invertebrate species, while CAP residues are expected to accumulate in soil due to its persistence in soil (half-life up to 1130 days in dissipation studies on bare ground, USEPA, 2008). Sharma et al (2014) reported an average initial CAP concentration in a sugarcane field soil of 0.88 mg/kg dw after the application of CAP at the recommended dose of 100 g a.i./ha. This indicates that exposure of soil invertebrates is likely to occur.…”
Section: Introductionmentioning
confidence: 99%
“…With the application of chlorantraniliprole at 100 and 200 g a.i. ha − 1 , the half-life values were calculated as 8.36 and 8.25 days, respectively (Sharma et al 2014).…”
Section: E Ciency Of the Methodsmentioning
confidence: 99%